Thymus research in relation to myasthenia gravis: a new perspective on cell subpopulations and future directions - Matsui, Naoko; Ohigashi, Izumi; Marx, Alexander (Frontiers in Immunology, 2025)
The thymus generates T cells from immature thymocytes and prevents autoimmune diseases through negative selection and the generation of FOXP3+ regulatory T cells (Tregs). The thymic architecture is typically divided into two distinct microenvironments, the cortex and the medulla. These microenvironments are characterized by the presence of cortical thymic epithelial cells (cTECs) and medullary thymic epithelial cells (mTECs), respectively. Recent single-cell and spatial transcriptomic analyses have revealed the expanding diversity of TEC subpopulations in mice and humans. Myasthenia gravis (MG) is an autoimmune disorder characterized by fatigue resulting from muscle weakness, which is caused by antibodies toward structures within the neuromuscular junction. The most common target of pathogenic autoantibodies in MG is the acetylcholine receptor (AChR). MG patients are prone to thymic abnormalities, including thymic follicular hyperplasia and thymoma. Previous studies have suggested that mTECs expressing major histocompatibility complex (MHC)/AChR–peptide complexes are involved in the intrathymic pathogenesis of this MG type. However, the exact mechanisms are unknown. This review provides an update on the diversity of TEC subpopulations and other cellular alterations in the MG thymus. Additionally, we present hypotheses on the pathogenetic pathways leading to MG and suggest potential future directions in thymus research.